Answer:
25
Step-by-step explanation:
Answer:
a) 15 ÷ 2/3=
=1 5 x 3/2=45/2
b) 3 × 1/8 × 6/9
=1/8 x 2( Simplify 3 with 9 remainder 3, reduce
6 with 3 remainder 2)
=1/4
c) 3 3/5 ÷ 2 2/5
=18/5 : 12/5
=18/5 . 5/12
=3/2
d) 2 1/12 × 1 1/5
= 25/12 . 6/5
=5/2
Step-by-step explanation:
Total mass = 6.08 x 10^23 * 1.67 x 10^-24 = 1.01536
Formula is y = a(x-h)^2 + k
Where h is 1 and k is 1
f (x) = a(x-1)^2 + 1
-3 = a(0-1)^2 + 1
-3 = a(-1)^2 + 1
-3 = a(1) + 1
-3 - 1 = a
-4 = a
a = -4
A must be equal to -4
y = -4(x-1)^2 + 1
0 = -4(x-1)^2 + 1
4(x^2 - 2x + 1) - 1 = 0
4x^2 - 8x + 4 - 1 = 0
4x^2 - 8x + 3 = 0
4x^2 - 8x = -3
Divide fpr 4 each term of the equation....x^2 - 2x = -3/4
We must factor the perfect square ax^2 + bx + c which we don't have. We must follow the rule (b/2)^2 where b is -2....(-2/2)^2 =
(-1)^2 = 1 and we add up that to both sides
x^2 - 2x + 1 = -3/4 + 1
x^2 - 2x + 1 = 1/4
(x-1)^2 = 1/4
square root both sides x-1 = (+/-) 1/2
x1 = +1/2 + 1 = 3/2
x2 = -1/2 + 1 = 1/2
x-intercepts are 1/2 and 3/2, in form (3/2,0); (1/2,0)
Answer: option B
Step-by-step explanation:
-4, 1, 3